Analysis Of The Implementation Of Management Information Systems In Budi Setia Langowan Hospital - Risca Manoppo (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
The rapid and extensive development and progress of information technology today, so that for an agency / company the information used as a basis for administration and data processing is an application system in various fields that are required to use the information system. Good service quality is the implementation of a reliable, effective and efficient Hospital Management Information System (SIMRS) and upgradeable. The hospital information system has an important role in clinical and administrative services. Hospitals that use a website-based system (SIMRS) are designed to integrate the main functions of the hospital into one integrated system stored in a database center. This study aims to analyze the implementation of a hospital information system using the PIECES method. The type of research used is qualitative.